Analisis Unsur-Unsur Intrinsik Cerita Pendek Tema Menyayangi Tumbuhan dan Hewan Pada Buku Siswa Kelas III SD - Santi Santi; Iis Nurasiah; Arsyi Rizqia Amalia (STKIP Andi Matappa Pangkep, 2021)
This study aims to analyze the intrinsic elements of the short story contained in the book of grade III elementary school students. In carrying out this research, a qualitative method was used to adapt the theory of analysis. The object of research is the intrinsic elements that make up the short story entitled The Sincere Apple Tree, The Story of Ants and Pigeons, Making and Caring for Hanging Plants, and The Mouse Deer and Crocodiles. The source of the data is in the theme book 2 Loving Plants and Animals. The research data collection uses the technique of data reduction stages, data presentation and conclusion. While in analyzing the data using the descriptive method of analysis. Based on data analysis, it can be described the intrinsic elements that make up the short stories, namely the theme, plot, characters, setting, and message. The results showed that all the short stories in the student books were in accordance with the intrinsic elements.